Energy alternatives - Cruden, Gabriel (Lucent library of science and technology., 2005)
Energy drives all life and is a key component to how humanity works, lives, and sustains itself. Due to the depletion of existing energy sources and the damage being done to the earth's ecosystems, renewable, non-polluting energy sources such as solar, wind, and geothermal power are being developed and implemented. This volume explores modern energy alternatives to traditional fossil fuels.